Jute (Corchorus species) and allied fibres research in India - DAS, B B; MAITI, S N (The Indian Journal of Agricultural Sciences, 2013)
India has the largest jute (Corchorus spp) area and production, and of late it surpassed all other major jute-growing countries. The productivity is more than 1.9 tonnes/ha. Some of the varieties of jute and other fibre crops released and currently in use are' JRC 321', 'JRC 212', 'JRC 7447', 'JRC 4444', 'UPC 94', 'KC I' and 'KTC I' of C. capsularis L.; 'JRO 632', 'JRO 7835', 'JRO 524', 'TJ 40', 'JRO 3690' and 'KOM 62' ofe. olitorius L.; 'HC 583' and 'AMC 108' ofkenaf(Hibiscus cannabinus L.); 'HS 4288'. 'HS 7910', 'AMY 1', 'AMV 2', 'AMV 3' and 'AMY 4' of roselle (H.sabdariffa L. ); 'R 67-34' of ramie (Boehmeria nivea Gaud.); and 'K 12' of sunnhemp (Crotafariajuncea L.). The article deals with the progress made after independence in jute and allied fibres with special reference to varietal improvement, production technology, retting, seed production and multiplication, diseases and pests and their controlmeasures as well as future thrust areas.